Kepuasan Pelayanan Penumpang Angkutan Udara Pada Badan Usaha Angkutan Udara Niaga Berjadwal Dalam Negeri di Bandara Soekarno-Hatta - Yudhi Halim; Sigit Priyanto; Latif Budi Suparma (Langit Biru: Jurnal Ilmiah Aviasi, 2023)
The flight performance at Soekarno-Hatta Airport will more or less reflect the overall flight performance in Indonesia. One of the most important aspects that becomes an indicator of its success is the aspect of passenger service. For that, this research needs to be done. The research was conducted on Domestic Scheduled Commercial Air Transport Business Entities for domestic routes in the category of minimum service class operating at Soekarno-Hatta Airport. This study aims to analyze the satisfaction of air transport passengers in the Air Transport Business Entity. The research was conducted using the Quantitative Method. Sample selection was done by using purposive sampling technique. Data were collected through questionnaires and field observations, and the data were analyzed using the Customer Satisfaction Index (CSI) method. The results of the analysis show that passengers are satisfied with the services of Lion Airlines (CSI=76.994%) and Citilink Indonesia (CSI=80.836%), and are very satisfied with the Super Air Jet service (CSI=82.023%).